Factors affecting the development of hydrocephalus in patients with decompressive craniectomy - Afreen, Mahrukh; Hussain, Syed Vaqar; Mustafa, Hussain (Journal of the Pakistan Medical Association, 2026)
Objective: To explore the relationship between decompressive craniotomy and hydrocephalus formation and identify the various factors leading to post-traumatic hydrocephalus in patients with traumatic brain injury. Methods: The prospective cohort study was conducted at the Department of Neurosurgery, Shifa International Hospital, Islamabad, Pakistan, from April 2023 to April 2024, and comprised patients regardless of age and gender who presented with traumatic brain injury to the emergency room and underwent a plain computed tomography of the brain to determine the management plan: conservative or decompressive craniotomy. Demographical, clinical, and radiological parameters were noted, including age, gender, Glasgow Coma Scale score on arrival, and midline shift on pre-operative scans. Data about the mean area/diameter of the bone flap, site of craniectomy, and medial midline margin of craniectomy on post-operative scans were also noted. An Evans ratio <0.3 was labelled as hydrocephalus on a post-operative scan done 6-8 weeks after decompressive craniotomy. Data was analysed using SPSS 21. Results: Of the 80 patients, mean age of 47.67±9.34 years, 43(53.75%) were males and 35(46.25%) were females. Overall, 25(31.25%) patients developed hydrocephalus. There was a significant association of hydrocephalus with Glasgow Coma Scale score 11-13 on arrival (p=0.004), midline shift >25mm at the time of hydrocephalus diagnosis (p=0.000), area of the bone flap (p=0.001), bilateral craniectomy (p=0.029), and medial margin of craniectomy <25mm (p=0.032). Conclusion: About one-third of traumatic brain injury patients undergoing decompressive craniotomy were found to have hydrocephalus, which had a significant association with Glasgow Coma Scale score on arrival, midline shift at the time of diagnosis, area of the bone flap, bilateral craniectomy, and medial margin of craniectomy. Key Words: Decompressive craniectomy, DC, Hydrocephalus, HCP, Glasgow Coma Scale, GCS, Post-traumatic hydrocephalus, PTH, Traumatic brain injury, TBI.